FLOUTING MAXIM OF QUANTITY IN THE CHARACTERS’ DIALOGUES IN “DETECTIVE PIKACHU” MOVIE - Desri Lestari; Dadan Firdaus (Universitas Islam Negeri Sunan Gunung Djati, 2021)
Detective Pikachu movie, a family genre movie, has universal cultural identity across countries even continents which is representative of internationally accepted movies through all ages and culture. Communication between speakers and listeners should fulfill maxims in order to have an effective communication and to avoid misunderstanding. The research uses Grice's theory of the Cooperative Principle in order to describe the communication that happens among the characters in the movie. The purpose of this research is: to find out maxim of quantity flouted in the characters’ dialogue in Detective Pikachu movie and to find out the other characters involved in the dialogue respond to this flouting maxim of quantity. The obtained data were analyzed with descriptive qualitative method. As the findings, there are 30 data flouting maxims of quantity has flouted in the characters dialogue in Detective Pikachu movie. Almost all of the characters in the movie flouted the maxim of quantity. The characters are said to be flouting the maxim of quantity because they are in the dialogue that occurs. They are too much or too little in providing information. When viewed from the comparison of the dialogue in the movie, giving too much information is more often done by the characters than giving too little information. the other hearer responds to the speaker who flouted the maxim of quantity is not to be bothered by this because it is helped by the implicature, insights and experiences of the characters so that the dialogue can still work well. Keywords: Pragmatics; Cooperative Principle; Flouting Maxim